Gas-Sensing Mechanism of Nanocrystalline Mesoporous Metal Oxide for Detection of volatile Organic Compounds - Abu, Mohamad Zailani Bakar (Universiti Sains Malaysia, 2015)
The utilization of mesoporous metal oxides as sensing materials which are synthesized via nanocasting (structure replication) method that gave an ordered and well-defined structures, high surface area and porosity, high crystallinity, small crystallite and grain size would be expected to be successfully applied in gas sensors by Improving their gassensing properties such as sensitivity, selectivity, stability and speed of response. The present works attempt to investigate the behavior of chemisorption and diffusion of the synthesized nanocrystalline mesoporous metal oxides powders In order to establish the gas-sensing mechanism. The correlation on the utilization of a zeolite layer as a membrane filter over the sensing materials is also investigated. Correlation between the gas-sensing performance and catalytic-oxidation activity of the gas sensors has been established in order to understand their sensing/ reaction piechanism in details. Date Tarikh